2014
DOI: 10.1007/s00128-014-1239-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorpyrifos and Endosulfan on Different Life Stages of the Freshwater Burrowing Crab Zilchiopsis collastinensis P.: Protective Role of Chorion

Abstract: The lethality (LC50) of endosulfan and chlorpyrifos is higher in adults (1990 and 156.78 μg/L respectively) than in embryos (95380 and 1242.54 μg/L respectively) of the crab Zilchiopsis collastinensis. The thickened embryonic coat of the freshwater species might isolate the embryo inside the egg, reducing the toxicity. Sublethal concentrations of chlorpyrifos and endosulfan caused an increase in hatching time and a decrease in effective hatching (p < 0.05), and only the control crabs survived until the first m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…The females of this species appear to be quite resistant to endosulfan. In previous studies conducted by us, the 96-h LC 50 of endosulfan was found to be 1902 mg/l (Negro et al, 2014). When Z. collastinensis was exposed to endosulfan for 22 days, accumulation of this pesticide was found to have occurred both in hepatopancreas and gonads, although there was a reduction with time of endosulfan concentrations in hepatopancreas (Negro et al, 2012).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The females of this species appear to be quite resistant to endosulfan. In previous studies conducted by us, the 96-h LC 50 of endosulfan was found to be 1902 mg/l (Negro et al, 2014). When Z. collastinensis was exposed to endosulfan for 22 days, accumulation of this pesticide was found to have occurred both in hepatopancreas and gonads, although there was a reduction with time of endosulfan concentrations in hepatopancreas (Negro et al, 2012).…”
Section: Introductionmentioning
confidence: 71%
“…The commercial product was diluted in dechlorinated water, added to each aquarium and gently homogenised throughout the tank. Based in the LC 50 of 1902 (1679-2124) mg endosulfan l À 1 , obtained in a 96 h exposure period test, three sublethal concentrations (about 1/20, 1/10 and 1/ 5) were used (Negro et al, 2014). Initial concentrations were 9476; 192710 and 360 715 mg endosulfan l À 1 (C 1 , C 2 and C 3 respectively).…”
Section: Assay Conditionsmentioning
confidence: 99%
“…These data indicate developmental differences in AChE expression and catalytic activity which may allow younger animals to be more resistant to OPs than older animals. Zebrafish embryos have a chorion that is present approximately the first 48 hpf (Kimmel et al, 1995) and several studies have demonstrated a protective role of the chorion for pollutant toxicity (Helmstetter and Alden, 1995;Kais et al, 2013;Negro et al, 2014). This implies that CPF uptake may be reduced until hatching occurs.…”
Section: Discussionmentioning
confidence: 96%
“…It has also been documented a low gene expression of antioxidant enzymes in D. rerio in response to prooxidants because of immature antioxidant and detoxi cation systems (Rodríguez-Fuentes et al 2015a). The chorion also plays an essential protective role (Embry et al, 2010;Negro et al, 2014). The chorion is present in the embryo of D. rerio until 48 hpf (Kimmel et al 1995); therefore, the organisms are directly exposed to the contaminants for a shorter time.…”
Section: Methodsmentioning
confidence: 99%